The Effect Of Stakeholder Pressure On Sustainable Performance Mediated By Eco-Innovation Practices - Omar, Salmah (2018)
Increasing awareness and global concerns on sustainability issues are striving the firms to improve their sustainability performance in order to satisfy multiple stakeholders.Firms are facing growing pressure to become “greener” and more environmentally friendly. This pressure is increasingly felt by high polluting industry,such as chemical industry.In Malaysia,the chemical industry is one of the main contributors to the country’s pollution index.Stakeholder pressures (SHP) are believed will affect the firm’s activities that will in turns affect their business performance.Therefore,firms have had to review their production processes as a result of pressures from the multiple stakeholders.Eco-innovation is a promising approach that decreases environmental impact and helps firms to sustain their business and the environment. Eco-innovation plays an important role in the implementation of sustainable development.The overall objective of eco-innovation is to reduce impact on the environment,as well as to create new market opportunities,products,services or processes aimed at improving environmental performance.However,eco-innovation practices (EIP) are still less implemented by chemical firms in Malaysia since many are still not aware of its essential to improve their sustainable performance (SP).Thus,this study was conducted among chemical firms in Malaysia with the aims to investigate the extent of stakeholder pressure and the implementation of eco-innovation practices which believed will affect the sustainable performance of the firms.This study also sought to treat the eco-innovation practices as a mediating factor on the relationship between stakeholder pressure and sustainable performance.To meet these objectives,a series of research hypotheses underpinned by theoretical basis of Stakeholder Theory,Legitimacy Theory and Natural-Resources-Based View Theory (NRBV) were proposed to be tested.A mail survey was used for data collection and responses from 73 chemical companies have been used for data analysis using SmartPLS 3.0.The result reveals that SHP and EIP significantly and positively affected all the component of sustainable performance (SP).While EIP has partially mediated the relationship between SHP and SP.This study also revealed the level of SHP and EIP among chemical firms in Malaysia is moderate to a considerable extent.The result also demonstrated that social benefit has the highest score on embracing the EIP compared to financial and other factors.This study provides some implication in terms of theory advancements and practical applications that can help practitioners to better understand the issues and contextual elements related to stakeholder pressure,eco-innovation practices and sustainable performance of the firms which will enhance their competitive advantage.